IL-6 and TNF-α salivary levels according to the periodontal status in Portuguese pregnant women - Vanessa Machado; Maria Fernanda Mesquita; Maria Alexandra Bernardo; Ester Casal; Luís Proença; José João Mendes (PeerJ, 2018)
Background Periodontitis is associated with increased concentration of inflammatory markers and saliva has been proposed as a non-invasive diagnostic fluid in oral and systemic diseases. The levels of salivary biomarkers, such as cytokines, could potentially be used to distinguish periodontal healthy individuals from subjects with periodontal disease. The purpose of this study was to characterize the salivary levels of two inflammatory biomarkers associated with periodontitis, interleukin-6 (IL-6) and tumour necrosis factor-alpha (TNF-α), in order to assess whether these cytokines salivary levels could potentially be used to complement periodontitis pregnant women diagnose. Methods Forty-four pregnant women were distributed into three groups, according to their periodontal status: healthy, mild/moderate periodontitis and severe periodontitis. Unstimulated saliva was collected and analysis of TNF-α and IL-6 salivary levels were performed with Immulite®. Results Women with periodontitis exhibited significantly higher levels (p = 0.001) of salivary IL-6 and TNF-α compared with the healthy group: 25.1 (±11.2) pg/mL vs. 16.3 (±5.0) pg/mL and 29.7 (±17.2) pg/mL vs. 16.2 (±7.6) pg/mL, approximately 1.5 and 1.8 times more, respectively. Additionally, cytokines were significantly increased (p < 0.05) in severe periodontitis compared to periodontal healthy pregnant women. Conclusions These results revealed that IL-6 and TNF-α salivary biomarkers provide high discriminatory capacity for distinguishing periodontal disease from periodontal health in pregnant women.